2010
DOI: 10.3866/pku.whxb20101213
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Selenomethionine and Copper Ions

Abstract: 有 4 个峰(峰 I, II, III, IV). 扫描电位从 600 mV 到-600 mV 时, Cu(II)-(SeMet)2 配合物在 14 mV 时被还原为 Cu(I)-SeMet 配合物; Cu(I)-SeMet 配合物在-194 mV 被还原为 Cu(0)和 SeMet. 由-600 mV 回扫时, 还原产物 被逐次氧化为 Cu(I)-SeMet 配合物(128 mV)和 Cu(II)-(SeMet)2配合物(271 mV). 同时发现 Cu(I)-SeMet 配合物 在电位-100 mV 至 200 mV 间是稳定的, Cu(I)的氧化还原过程被观察到. 此外, 采用毛细管电泳法测得二元 Cu-SeMet 配合物的稳定常数(K1和 K2)分别为 2.24×10 7 和 2.24×10 6. 最后, 推测 Cu-SeMet 配合物的结构为: 在 pH 3.9 时, 铜离子通过 Cu-Se 和 Cu-OCO 键与 SeMet 发生配位作用; 在生理条件时, 铜离子通过 Cu-N 和 Cu-OCO 键与 SeMet 发生配位作用.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Therefore, high pressure heat treatment has attracted more and more attention. Most research has focused on the high pressure heat treatment effects on the phase transformation during alloy solidification [4][5][6][7][8]. Recent work showed that high pressure heat treatment applied during the solid-state phase transformation of Cu-alloy can also change the microstructure of the alloy [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high pressure heat treatment has attracted more and more attention. Most research has focused on the high pressure heat treatment effects on the phase transformation during alloy solidification [4][5][6][7][8]. Recent work showed that high pressure heat treatment applied during the solid-state phase transformation of Cu-alloy can also change the microstructure of the alloy [9][10].…”
Section: Introductionmentioning
confidence: 99%